Fox tale - Foreman, Michael, 1938- (London : Andersen Press, 2007)
A young fox cub and his siblings journey with their father to a place where a kind old man brings them food, but one day the old man is attacked by a gang of boys.
3.0
K-3
Keywords: Foxes -- Juvenile fiction; Foxes -- Fiction; Foxes -- Fiction